Analysis of molecular diversity in tomato (Solanum lycopersicum) genotypes using SSR primers - SINGH, B; GOSWAMI, AAKANSHA (The Indian Journal of Agricultural Sciences, 2014)
Tomato (Solanum lycopersicum L.) was sown during October 2010 at Department of Horticulture, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, for developing the nursery. After that the single plantlet of each variety was transferred and maintained into the separate pots for using conventional agronomic practices to keep the crop in good condition. Study of morphological and molecular diversity in landrace collections was carried out during 2010. Germplasm collections of all the 24 genotypes including determinate and indeterminate cultivars of tomato were screened with twenty SSR (simple sequence repeat) primers in order to determine genetic identities, genetic diversity and genetic relationships. On the basis of resolving power, primer A-8, A-13 and A-19 were most significant as they are able to recognize all 24 genotypes. The gene diversity was varied from 0.65 to 0.97 values with a mean diversity of 0.84. On an average, 54 scorable and reproducible alleles were amplified using all primers. Cluster analysis clearly showed the genetic diversity among the genotypes under study.